2020
DOI: 10.1108/ijtc-09-2019-0156
|View full text |Cite
|
Sign up to set email alerts
|

Unusual venues for business events: key quality attributes of museums and art galleries

Abstract: Purpose This paper aims to identify the key quality attributes a museum or art gallery should possess and enhance to become an attractive business event venue. Design/methodology/approach The research adopted a two-stage case-study methodology. Firstly, three museums were selected in Manchester, UK, to explore the venues’ approaches to hosting business events. These were the Lowry Art Centre, Salford Museum and Manchester Art Gallery. Secondly, a business event at another museum in the city, Science and Indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Roult, Auger & Lafond, 2020), and they tend to consider single spaces in the city rather than the overall supply of event space. Antchak & Adams (2020) note the growing use of museums and art galleries as "unusual venues" for business events, and Nolan (2020) found that the supply of business events venues has grown with the development of purpose-built event space. She also notes the emergence of the hybrid venue, or blended use of a physical space and virtual reality.…”
Section: Methodsmentioning
confidence: 99%
“…Roult, Auger & Lafond, 2020), and they tend to consider single spaces in the city rather than the overall supply of event space. Antchak & Adams (2020) note the growing use of museums and art galleries as "unusual venues" for business events, and Nolan (2020) found that the supply of business events venues has grown with the development of purpose-built event space. She also notes the emergence of the hybrid venue, or blended use of a physical space and virtual reality.…”
Section: Methodsmentioning
confidence: 99%
“…As soon as the concept of metaverse became popular, many companies attempted to develop business and design products related to the metaverse, such as Baidu and Tencent (Fu, 2022). In urban tourism, museums and art galleries are important venues for leisure and business activities (Antchak & Adams, 2020). In China, some history and culture exhibitions are positively combined with metaverse for providing an immersive experience to tourists.…”
Section: Metaversea New Way To Attract Urban Touristsmentioning
confidence: 99%
“…Events include arenas where interactions between show-makers and consumers occur in the context of particular physical environments [12]. Event characteristics such as interactivity, utilization of technology, excitement, and physical environment can work in tandem to produce engaging experiences that delight visitors, or ineffective ones that underwhelm them [13]. Experience quality can be assessed by the implication of functional and emotional aspects in equal contexts [14].…”
Section: Museum Event Qualitymentioning
confidence: 99%